Estudo das propriedades vibracionais e polimorfismo de sistemas do tipo A4W11O35 (onde A= Cs, Rb) por espectroscopia Raman - Silva, Katiane Pereira da (2010)
The compounds Cs4W11O35 (CW) and Rb4W11O35 (RW) belong to the class of hexagonal bronzes whose structure originates from KxWO3 superconductor hexatungstate. Charge imbalanced tungsten bronzes are dielectric materials with rich polymorphism, ferroelectric properties and second harmonic generation. In this work we report polarized Raman spectra results for both CW and RW as well as results of high pressure Raman scattering experiments (0.0 11.0 GPa) for Cs4W11O35 system, for which we have observed two structural phase transitions at about 4 GPa and 7.5 GPa. We discuss these transformations and polarized Raman spectra, on basis on lattice dynamics calculation in the related system KNbW2O9. Polarized Raman spectra provide strong indicative that the highest wavenumber modes observed in these systems originates from tungsten or oxygen vacancies. The observation of a soft-like mode indicates that the observed phase transitions exhibit a displacive type behavior, thus further indicating that these transformations are likely related to reorientations of octahedral units. The soft mode nature is discussed as well. Additional, measurement of temperature dependent Raman spectra shows that the structure of CW is stable op to 800 K. Low temperature measurements reveal the existence of a new phase below 190 K. Temperature transformation lead the structure to a higher symmetric phase below 190 K.